2012
DOI: 10.1007/s00268-012-1821-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity and Decompressive Laparotomy on Mortality in Acute Pancreatitis Requiring Intensive Care Unit Admission

Abstract: BackgroundControversy still exists on the effect that obesity has on the morbidity and mortality in severe acute pancreatitis (SAP). The primary purpose of this study was to compare the mortality rate of obese versus nonobese patients admitted to the ICU for SAP. Secondary goals were to assess the potential risk factors for abdominal compartment syndrome (ACS) and to investigate the performance of validated scoring systems to predict ACS and in-hospital mortality.MethodsA retrospective cohort of adults admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 105 publications
1
43
1
Order By: Relevance
“…The mortality rate of acute pancreatitis with complication of ACS varies depending on the report , but a systematic review by van Brunschot et al showed a high mortality rate of 47.5% . Also, a large number of complications from organ disorder/failure have been shown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate of acute pancreatitis with complication of ACS varies depending on the report , but a systematic review by van Brunschot et al showed a high mortality rate of 47.5% . Also, a large number of complications from organ disorder/failure have been shown.…”
Section: Resultsmentioning
confidence: 99%
“…The mortality rate of regional pancreatic infection complicated with ACS is reported to be 24.0–66.7% . Acute pancreatitis with excessive fluid infusion, high severity, renal disorders, creatinine levels, complications of respiratory disorders, tachypnea, and fluid collection in multiple areas, as observed by CT, is likely to develop IAH/ACS , and the measurement of IAP over time is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…Another study that included patients under the age of 30 who were not previously ill showed that sex had no influence on IAP values (14). It was previously shown that increased BMI leads to the increase of IAP (15)(16)(17)(18) and an increase of 1 kg/m 2 in BMI leads to the increase of 0.07 mmHg of IAP (15). The increase of BMI is correlated to the increase of IAP, but it was also shown that it does not depend on sex or race (15).…”
Section: Discussionmentioning
confidence: 98%
“…Results clearly showed that early decompression (first 4 days) was associated with significantly less deaths, compared with late decompression (after 4 days). Davis et al [ 12 ] reported 25% mortality in surgically decompressed patients with ACS. Mean time from diagnosis to surgical intervention in their study was 3.1 h. It seems that early surgical decompression in patients with ACS during SAP may be associated with less mortality rate.…”
Section: Interventional Treatmentmentioning
confidence: 99%